PREGNANCY AND INEQUALITIES: : THE IMPACT OF CULTURE ON WOMEN'S EDUCATION AND WORK (Interdisciplinary Studies Journal, 2025)
Pregnancy and motherhood, although natural parts of many women's lives, continue to be marked by specific inequalities in access to education and work. The impact of culture, combined with the lack of effective public policies, reinforces cycles of exclusion and limitations that affect not only women but also society as a whole.The aim of this study is to analyze the cultural and institutional impacts on pregnant women in relation to education and the labor market, evaluating the effectiveness of existing public policies and identifying solutions that promote inclusion and equal opportunities for pregnant women.The methodology used for this study was a literature review, based on research in bibliographic databases.The results indicate that cultural norms still associate motherhood with exclusive home care, generating stigma and barriers to access to education and employment.Public policies such as maternity leave and access to daycare centers have limited effectiveness, especially in vulnerable contexts where many women remain unassisted.It is concluded that, in order to promote the inclusion of pregnant women in education and the labor market, it is necessary to strengthen public policies and break down gender stereotypes.
Keywords: Culture; Communication; Restorative Practices; Individual Identities; Collective Identities